2000
DOI: 10.1084/jem.192.10.1391
|View full text |Cite
|
Sign up to set email alerts
|

Granzyme B–Mediated Cytochrome C Release Is Regulated by the Bcl-2 Family Members Bid and Bax

Abstract: Cytotoxic T lymphocytes (CTLs) destroy target cells through a mechanism involving the exocytosis of cytolytic granule components including granzyme B (grB) and perforin, which have been shown to induce apoptosis through caspase activation. However, grB has also been linked with caspase-independent disruption of mitochondrial function. We show here that cytochrome c release requires the direct proteolytic cleavage of Bid by grB to generate a 14-kD grB-truncated product (gtBid) that translocates to mitochondria.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
219
0
2

Year Published

2000
2000
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 282 publications
(232 citation statements)
references
References 72 publications
(159 reference statements)
11
219
0
2
Order By: Relevance
“…Our observations are consistent with previous reports. 25,26 We further showed that Bid was not processed to tBid in GzmF-loaded cells, whereas Bid was activated to tBid by GzmB treatment (Figure 6b). Caspase-3 was probed as a positive control for GzmB.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Our observations are consistent with previous reports. 25,26 We further showed that Bid was not processed to tBid in GzmF-loaded cells, whereas Bid was activated to tBid by GzmB treatment (Figure 6b). Caspase-3 was probed as a positive control for GzmB.…”
Section: Resultsmentioning
confidence: 92%
“…Cyt c release induced by GzmB or GzmK is through the processing of Bid to tBid. 22,25 However, GzmF cannot activate Bid to tBid in the induction of death. Cyt c was still released in Bid À/À and Bax/Bak DKO MEF cells with GzmF treatment but was not released with GzmB treatment.…”
Section: Discussionmentioning
confidence: 99%
“…It induces target cell apoptosis by activating the caspases, particularly the key executioner caspase, caspase-3 (143,144) (Figure 3). Human GzmB, but not the mouse enzyme, also activates cell death by directly cleaving the key caspase substrates, bid and ICAD, to activate the same mitochondrial and DNA damage pathways, respectively, as the caspases (53,(145)(146)(147)(148)(149)(150)(151) (Figure 3). As a consequence, caspase inhibitors have little effect on human GzmB-mediated cell death and DNA fragmentation, whereas the same inhibitors significantly block the action of the mouse enzyme.…”
Section: Granzyme Bmentioning
confidence: 99%
“…18,28 These experiments demonstrated that human GrB proteolytically activated Bid at aspartate 75 , resulting in its translocation to the mitochondrial outer membrane, and the facilitation of oligomerization of Bax/Bak molecules. [29][30][31] It was initially thought that this resulted in the release of cytochrome C and apoptosome formation. This proved not to be the case, but rather involved inhibitor of apoptosis proteins (IAPs) that are potent antagonists of caspase activity.…”
Section: Mechanisms Of Cytotoxicity and Physiological Roles Of Grsmentioning
confidence: 99%